2018
DOI: 10.3390/separations5020031
|View full text |Cite
|
Sign up to set email alerts
|

Food Sample Preparation for the Determination of Sulfonamides by High-Performance Liquid Chromatography: State-of-the-Art

Abstract: Antibiotics are a common practice in veterinary medicine, mainly for therapeutic purposes. Sectors of application include livestock farming, aquacultures, and bee-keeping, where bacterial infections are frequent and can be economically damaging. However, antibiotics are usually administered in sub-therapeutic doses as prophylactic and growth promoting agents. Due to their excessive use, antibiotic residues can be present in foods of animal origin, which include meat, fish, milk, eggs, and honey, posing health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(22 citation statements)
references
References 60 publications
(130 reference statements)
0
17
0
Order By: Relevance
“…However, the improper administration of sulfa drugs in dairy husbandry and the insufficient withdrawal periods can lead to noncompliant residues in animal originated foods, a fact which can contribute to several concerns in the dairy industry and public health [4].…”
Section: Introductionmentioning
confidence: 99%
“…However, the improper administration of sulfa drugs in dairy husbandry and the insufficient withdrawal periods can lead to noncompliant residues in animal originated foods, a fact which can contribute to several concerns in the dairy industry and public health [4].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the extensive use of antibiotics in animals, reliable data about the pattern of use and the quantity of these compounds are not always available [ 22 ]. That is why it is important to monitor the concentration levels of antibiotic residues in animals and in food products of animal origin [ 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. Studies on the quantitative risk assessment of foods provide important frameworks to address some of the issues related to the risk to human health from the intake of various residues via food [ 32 , 33 , 34 , 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these problems, chromatographic techniques, such as high-performance liquid chromatography (HPLC), was developed and known to be the most reliable, sensitive and robust method [2123]. Available litreture showed that, HPLC was able to determine sulfonamides from food samples [24] and also HPLC method was successfully used to detect the antibiotic residues at lower than their respective maximum residue limits values [25]. Thus, in the present study the microbiological assay was first carried out to detect the presence of antibiotic residues in the cow milk samples collected from different farms in Dharwad district of Karnataka, India.…”
Section: Introductionmentioning
confidence: 99%